2013
DOI: 10.1177/1477153513512501
|View full text |Cite
|
Sign up to set email alerts
|

Luminance gradient for evaluating lighting

Abstract: This paper introduces luminance gradient as a metric for evaluating common non-uniform luminous environments. Luminance gradient is defined as the largest change rate and the polarity of spatial luminance variation on a large surface or across the entire field of view in high resolution. The metric, a visualization method, and a freely available MatLab code for plotting luminance gradient maps have been developed. The retinal resolution of pixels for mapping luminance gradient has also been identified. A camer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 12 publications
0
17
0
1
Order By: Relevance
“…High Dynamic Range). Związek wyników pomiarów w odniesieniu do aparatu wzroku człowieka jest jednak zbyt rzadko dostrzegany [14] i najczęściej nie jest wystarczająco eksponowany. Zdaniem autora artykułu, aby jednoznacznie rozwiązać problem wiarygodności wyników pomiarów, w pierwszej kolejności należy przybliżyć obecnie wykorzystywane technologie, przeprowadzając analizę możliwości pomiarowych, obliczeniowych i kalibracyjnych istniejących urządzeń.…”
Section: Wstępunclassified
“…High Dynamic Range). Związek wyników pomiarów w odniesieniu do aparatu wzroku człowieka jest jednak zbyt rzadko dostrzegany [14] i najczęściej nie jest wystarczająco eksponowany. Zdaniem autora artykułu, aby jednoznacznie rozwiązać problem wiarygodności wyników pomiarów, w pierwszej kolejności należy przybliżyć obecnie wykorzystywane technologie, przeprowadzając analizę możliwości pomiarowych, obliczeniowych i kalibracyjnych istniejących urządzeń.…”
Section: Wstępunclassified
“…To use camera as a sensor for luminance measurement, a camera has to be calibrated by any one of the methods available. Calibrations of raw HDR images can be done in the following ways [2]: 1)Vignetting correction ii) Photometric calibration using a calibration factor (CF).Based on the conversion factor method the relation of actual and scene luminance value is obtained here. To obtain the CF integrating sphere or selection of calibration curve for minimum error using color checker chart method can be taken.…”
Section: Camera Calibrationmentioning
confidence: 99%
“…For color surfaces the average error can be form 9.3 % to 13.1%. High Dynamic Range photography help to measure and interpret the spatiotemporal distribution of luminance in line with visual perception [2]. Newsham G R and Arsenault C D [3] demonstrated that a single Complementary Metal Oxide Semiconductor (CMOS) camera chip can replace the multiple sensors required by conventional systems for daylight harvesting, shading control and occupancy sensing.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations